Preaching Messages of Tapai Feast Tradition Welcoming Ramadan in Batu Bara Regency, Indonesia - Sabila Husna Lubis; Muhammad Husni Ritonga; Irma Yusriani Simamora (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2026)
Pesta Tapai tradition embodies Islamic values and cultural symbols whose meanings remain underexplored through a Symbolic Interactionist perspective. Research objective to analyze Islamic value internalization and symbolic meanings within Pesta Tapai through Symbolic Interactionism and da'wah communication. This study employed a qualitative descriptive approach. Data were collected through observation, in-depth interviews, and documentation of Malay community members in Batu Bara who actively participated in the Pesta Tapai tradition. The findings indicate that Pesta Tapai serves as an effective medium for cultural da'wah to internalize Islamic values, including ukhuwah Islamiyah, togetherness, cooperation, and social solidarity. These values are manifested through collective activities in preparing and sharing tapai and lemang before Ramadan. The tradition also contains rich symbolic meanings reflected in tapai, lemang, communal gatherings, and the mogang ritual. Tapai is interpreted as a symbol of patience, self-control, and spiritual readiness for Ramadan. From a Symbolic Interactionist perspective, community members collectively interpret cultural symbols, internalize them into religious identities, and transmit Islamic values across generations through sustained social interactions. Conclusion: Pesta Tapai serves as both a cultural tradition and a da'wah medium, strengthening the internalization of Islamic values through symbolism. Significance: The study enriches Islamic communication, cultural anthropology, and Symbolic Interactionism scholarship regarding local religious value transmission.